Restorative Justice in Domestic Violence Cases: Law Implementation and Challenges in Indonesia - Tuti Susilawati; Setiadi, Edi; Darusman, Yoyon (Sinergi International Journal of Law, 2025)
Despite Law Number 23 of 2004, the problem of domestic violence (KDRT) remains unsolved. The majority of victims of domestic violence are women, and the retributive method of punishment is believed to be less effective in protecting them. The purpose of this research is to examine how well the restorative justice policy in Indonesia complies with current legislation and how it helps victims of domestic violence regain their rights. This study explores the possibility of adopting restorative justice through the use of normative legal research methodologies that take a legislative approach and conduct a literature review. By facilitating healing for victims and offenders and facilitating reconciliation, the study found that restorative justice could be a mnore compassionate alternative. But there are a lot of problems with putting it into practice, including the fact that police officers don't comprehend it and that mediators need training. Thus, in order to guarantee that restorative justice is effectively implemented, training is necessary for mediators as well as community and law enforcement outreach.